Identification of Factors of Small Enterprise Coffee Development: A Case Study in UUT Agro Semesta, Bali - Widari Upadani, I Gusti Ayu; Putri Srinadi, Ni Luh; Aditya Krisnawan, Gusti Ngurah (International Journal of Management Science and Information Technology, 2026)
This research aims to identify the critical internal and external factors influencing the development of coffee MSMEs and to formulate strategic recommendations for UUT Agro Semesta in Pajahan Village, Tabanan, Bali. Addressing the slow growth and conventional management practices in the region's coffee sector, this study contributes to the field of management science by providing a strategic framework for small enterprise sustainability. The study employed a quantitative case study design, collecting primary data through structured questionnaires, interviews, and observations from 30 respondents selected via purposive sampling. Data analysis was conducted using SPSS Version 25 for descriptive statistics and the SWOT framework, involving Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) matrices. The results reveal that the enterprise possesses strong internal foundations (IFAS score: 2.93), primarily driven by specialized farmer skills and high family involvement (90%). However, external analysis (EFAS score: 3.10) highlights significant opportunities in government subsidies and cooperative networks, contrasted by threats from market access barriers (90% reported obstacles) and climate dependency. The findings suggest that the business is in a growth-oriented position, recommending an S-O (Strengths-Opportunities) strategy that prioritizes the utilization of government-led technical training to enhance production and leveraging cooperatives for market expansion. Practically, this study recommends that policymakers facilitate micro-financing and climate-adaptive irrigation technologies to mitigate technical weaknesses. These results offer a roadmap for coffee MSMEs to improve competitive advantage through integrated management and strategic institutional collaboration.